(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The article deals with the questions of the rationality of the dynamics planning process in operating and marketing activities of enterprises, substantiated the existence of interdependence between a number of processes and phenomena. The mathematical apparatus is being studied, which allows to analyze the production capabilities of enterprises, as well as have been formed the main requirements to the economic-mathematical model of regulation of production-business activities of the entity: the nonlinearity of the nature of dependence; inclusion of the investment factor; taking into account expectations in relation to the perspective change of demand dynamics at the market. Obtained a functional dependence, which would allow investigating the value of sales in relation to investment and demand for all the retrospective periods during which observations were made. Suggested the indicator, which allows determining whether it is expedient to regulate the production and economic activity of the enterprise.